Sodium-ion battery diaphragm, preparation method thereof and sodium-ion battery

The lack of heat resistance and adhesion of the separator is solved by using a combined coating of fluoropolyimide microspheres, sodium ion solid electrolytes, gelatable polymers and plasticizers on the sodium ion battery separator. The problem is that the thermal stability and cycling performance of the battery is improved, the risk of short circuit is reduced, and the safety and energy density are enhanced.

CN119315216AActive Publication Date: 2025-01-14GUANGDONG HAISIDA NAXING TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310847546.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

The sodium ion battery separator has poor heat resistance and low adhesion, which leads to battery short circuits and safety hazards, affecting circulation performance and stability.

Method used

Using a combined coating of fluoropolyimide microspheres, sodium ion solid electrolytes, gelable polymers and plasticizers, it is coated on both sides of the base film to improve the thermal stability and hot pressing bonding of the separator. performance.

Benefits of technology

It significantly improves the thermal stability and bonding performance of the diaphragm, reduces the risk of battery short circuit, enhances the cycling performance and safety of the battery, and improves energy density and power safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315216A_ABST
    Figure CN119315216A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery diaphragms, and discloses a sodium ion battery diaphragm, the diaphragm comprises a base membrane and coatings on two sides of the base membrane, and the coatings comprise fluorine-containing polyimide microspheres, a sodium ion solid electrolyte, a gelling high-molecular polymer and a plasticizer. The sodium-ion battery diaphragm provided by the invention has good thermal stability, relatively low diaphragm internal resistance and good hot-pressing bonding performance, the problems of poor cycle performance, electrolyte leakage and the like in the use process of a sodium-ion battery can be effectively improved, and the electricity utilization safety of the sodium-ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery diaphragms, and in particular to a sodium ion battery diaphragm and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Sodium-ion batteries have the advantages of low cost, environmental friendliness, long cycle life, and stable performance, and play a prominent role in energy storage, low-speed electric vehicles, etc. As a key material affecting the performance of sodium-ion batteries, sodium-ion battery separators are increasingly attracting the attention of scientific researchers.

[0003] As one of the key components of sodium-ion batteries, the diaphragm prevents the positive and negative electrodes from contacting, prevents battery short circuits, and transmits sodium ions. It is an important determinant of battery capacity, cycle capacity, and safety performance. At present, the main problems of sodium-ion battery diaphragms are as follows:

[0004] (1) During the use of sodium-ion batteries, local temperatures may be too high, and the sodium-ion battery diaphragm may shrink due to heat, resulting in local direct contact between the positive and negative electrodes, which in turn causes a battery short circuit, leading to explosion and combustion of the sodium-ion battery, posing a very serious safety hazard.

[0005] (2) The bonding force between the diaphragm and the positive and negative electrodes is weak, which causes the sodium-ion battery to deform or become soft, thereby affecting the stability and safety of the sodium-ion battery.

[0006] Therefore, it is of great research significance to study a sodium ion battery separator with high heat resistance and high adhesion. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of poor heat resistance and low adhesion of the sodium ion battery separator in the prior art, and to provide a sodium ion battery separator having good thermal stability and hot pressing bonding performance, thereby further improving the cycle performance of the sodium ion battery.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a sodium ion battery separator, wherein the separator comprises a base film and a coating on both sides of the base film; the coating comprises fluorinated polyimide microspheres, a sodium ion solid electrolyte, a gelable polymer and a plasticizer.

[0009] A second aspect of the present invention provides a method for preparing a sodium ion battery separator, comprising the following steps:

[0010] (1) stirring and mixing a mixed solution of a gelable polymer and a plasticizer with a mixed dispersion of a sodium ion solid electrolyte and fluorinated polyimide microspheres to obtain a coating slurry;

[0011] (2) The coating slurry is coated on both sides of the base film, and the sodium ion battery separator is obtained after drying.

[0012] The third aspect of the present invention provides a sodium ion battery separator prepared according to the method described in the second aspect.

[0013] A fourth aspect of the present invention provides a sodium ion battery, wherein the sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm, and the diaphragm is the diaphragm described in the first aspect or the diaphragm described in the third aspect.

[0014] Through the above technical solution, compared with the prior art, the present invention has the following beneficial effects:

[0015] (1) The sodium ion battery separator provided by the present invention has a surface density of fluorinated polyimide microspheres in the coating layer that is lighter than that of ordinary ceramics, which is beneficial to improving the energy density of the battery; the addition of sodium ion solid electrolyte can supplement sodium and play a certain role in reducing the internal resistance of the separator. At the same time, the synergistic effect between the fluorinated polyimide microspheres and the sodium ion solid electrolyte effectively improves the thermal stability of the base membrane and has better safety performance.

[0016] (2) The sodium ion battery separator provided by the present invention has a gelable high molecular polymer in the coating so that the prepared separator has the characteristic of absorbing electrolyte and gelling. The synergistic combination with the plasticizer and the fluorinated polyimide microspheres can also have good hot pressing bonding performance, which is beneficial to improving the sodium ion battery interface cycle performance and leakage risk.

[0017] (3) The sodium ion battery separator provided by the present invention has the characteristics of good thermal stability and strong hot pressing bonding performance. Among them, when maintained at a temperature of 150°C for 0.5h, the transverse shrinkage rate is 0-5%, and the longitudinal shrinkage rate is 0-5%; the bonding performance between the separator and the positive electrode sheet is 10-60N / m; the bonding performance between the separator and the negative electrode sheet is 10-60N / m. The high bonding performance makes it difficult for the positive electrode sheet / negative electrode sheet of the sodium ion battery to deform during long-term use, and the low thermal shrinkage rate of the separator can effectively prevent the short circuit problem inside the battery.

[0018] (4) The method for preparing the sodium ion battery separator provided by the present invention adopts a low-boiling point organic solvent combined with temperature and humidity oven drying to prepare the coating, which has a simpler process and is easy to operate.

[0019] (5) The sodium ion battery diaphragm prepared by the method provided by the present invention has good thermal stability, low diaphragm internal resistance and good hot pressing bonding performance, which can effectively improve the problems of poor cycle performance and electrolyte leakage during the use of sodium ion batteries, thereby improving the power safety of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a morphology diagram of the fluorinated polyimide microspheres prepared by the present invention. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] A first aspect of the present invention provides a sodium ion battery separator, wherein the separator comprises a base film and a coating on both sides of the base film; the coating comprises fluorinated polyimide microspheres, a sodium ion solid electrolyte, a gelable high molecular polymer and a plasticizer.

[0023] In the present invention, the coating is coated on both sides of the base film, retaining the excellent high-temperature closed-cell function of the porous base film, which plays a role in timely preventing the battery from short-circuiting; the synergistic effect of the fluorinated polyimide microspheres and the sodium ion solid electrolyte in the coating can effectively improve the thermal shrinkage performance of the diaphragm; the fluorinated polyimide microspheres can improve the peeling strength of the coating, and compared with ordinary ceramic particles, both are lighter in weight, which is beneficial to the improvement of energy density; the sodium ion solid electrolyte can play a role in sodium supplementation and reduce the internal resistance of the diaphragm; the gelable high molecular polymer improves the liquid absorption and gelation ability of the electrolyte and the performance of hot pressing bonding, which is beneficial to improving the interface performance; the addition of plasticizer can improve the peeling strength and plasticity of the coating.

[0024] According to the present invention, the glass transition temperature of the fluorinated polyimide microspheres is 200-350° C., the melting point is >300° C., and the average particle size is 0.05-10 μm, preferably 0.7-4 μm.

[0025] In the present invention, the preparation method of the fluorinated polyimide microspheres is:

[0026] Weigh the sulfone-containing diamine 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]sulfone and monomer A, dissolve the sulfone-containing diamine in a polar solvent, add monomer A in batches, and synthesize a polyamic acid solution in an ice-water bath. Prepare polyamic acid microspheres by electrostatic spraying in an electric field, then place them in a high-temperature hot furnace for imidization treatment, and naturally cool to room temperature to obtain fluorinated polyimide microspheres.

[0027] The monomer A is selected from at least one of pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA), and 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA).

[0028] Wherein, the solvent is selected from at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone and acetone.

[0029] The molar ratio of the monomer A to the sulfone-containing diamine 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]sulfone is 1.010-1.020, preferably 1.015.

[0030] Wherein, the solid content of the polyamic acid solution is 5-18%, preferably 15%.

[0031] Wherein, the electric field strength of the electrostatic spray is 0.5-5 kV / cm, preferably 1 kV / cm.

[0032] The conditions of the imidization treatment include: temperature of 180-300° C. and time of 10-60 min.

[0033] Wherein, the average particle size of the fluorinated polyimide microspheres is 0.05-10 μm, preferably 0.7-4 μm.

[0034] In the present invention, the fluorinated polyimide microspheres have a high melting point and glass transition temperature. Therefore, adding the fluorinated polyimide microspheres to the coating can improve the heat resistance of the sodium ion diaphragm, and the thermal shrinkage of the diaphragm becomes smaller. At the same time, the polar functional groups in the fluorinated polyimide microspheres improve the compatibility between the coating and the base film, and the peel strength with the base film is also improved, further improving the thermal stability of the sodium ion diaphragm.

[0035] In the present invention, the particle size of the fluorinated polyimide microspheres will affect the dispersion effect, and further affect the coating effect and thermal stability of the coating. The smaller the particle size, the better the dispersion effect. However, when the particle size is too small, the system becomes thicker under the same conditions due to the increase in specific surface area, which will also affect the dispersion effect and deteriorate the dispersion; if the particle size is too large, the dispersion stability will deteriorate and the thickness of the coating will be limited, and the required performance requirements cannot be achieved.

[0036] According to the present invention, the mass ratio of the gelable high molecular polymer to the plasticizer is 90-95:5-10.

[0037] According to the present invention, the mass ratio of the fluorinated polyimide microspheres to the sodium ion solid electrolyte is 50-90:10-50.

[0038] According to the present invention, the total mass of the fluorinated polyimide microspheres and the sodium ion solid electrolyte is calculated as A, the total mass of the gelable polymer and the plasticizer is calculated as B, and the mass ratio of A:B is 50-90:10-50.

[0039] The applicant found in the study that when the mass ratio of fluorinated polyimide microspheres, sodium ion solid electrolyte, gelable polymer and plasticizer in the coating satisfies the above relationship, the thermal stability and hot pressing bonding performance of the sodium ion separator are optimal.

[0040] In the present invention, the synergistic effect between the fluorinated polyimide microspheres in the coating and the sodium ion solid electrolyte can effectively improve the thermal stability of the base film and provide better safety performance.

[0041] In the present invention, the synergistic combination of the gelable high molecular polymer, the plasticizer and the fluorinated polyimide microspheres in the coating can simultaneously have good hot pressing bonding properties, which is beneficial to improving the interfacial cycle performance and leakage risk of the sodium ion battery.

[0042] According to the present invention, the thickness of the diaphragm is 9-52 μm, the thickness of the base film is 5-40 μm, and the thickness of the coating is 2-6 μm. Preferably, the thickness of the diaphragm is 9-20 μm, the thickness of the base film is 5-12 μm, and the thickness of the coating is 2-4 μm.

[0043] In the present invention, the thickness of the diaphragm is the sum of the thickness of a base film and the thickness of two coating layers. The thinner the diaphragm is, the more conducive it is for solutes to pass through, thereby increasing the energy density and reducing the impedance of the battery. However, as the thickness of the diaphragm decreases, the mechanical properties of the diaphragm will deteriorate, making it more likely that material dropped from the electrode or dendrites will pierce the diaphragm and cause a physical short circuit, resulting in a safety accident.

[0044] In the present invention, if the coating thickness is too small, it is difficult to achieve the required performance requirements; if the coating thickness is too thick, it will be unfavorable for the solute to pass through, reduce the energy density and increase the impedance of the battery. Under the condition of meeting the performance requirements, the thinner the coating, the better.

[0045] According to the present invention, the diaphragm is maintained at a temperature of 150° C. for 0.5 h, with a transverse shrinkage rate of 0-5% and a longitudinal shrinkage rate of 0-5%.

[0046] In the present invention, the test method for the thermal shrinkage rate of the diaphragm is:

[0047] Cut a square diaphragm of 10cm×10cm in size, locate 4 points at the center of the four sides 1cm away from the edges, and measure the distance between the two points in TD (transverse) and MD (longitudinal) through an optical microscope, and record them as Lh0 and Lz0. Then put 3 A4 papers on the top and bottom of the cut diaphragm and place it in a blast oven at a temperature of 150℃ (±1℃) for 0.5h. After heating, take out the diaphragm, and after the diaphragm returns to room temperature, measure the distance between the two points in the transverse and longitudinal directions through an optical microscope again, and record them as Lh and Lz. Calculate the transverse and longitudinal shrinkage rates of the diaphragm according to the following formulas 1 and 2 respectively, and take the average of the three test results as the thermal shrinkage rate of the diaphragm.

[0048] Thermal shrinkage in the longitudinal direction of the diaphragm: △Lz=(Lz0-Lz) / Lz0×100%(Formula 1)

[0049] Thermal shrinkage in the transverse direction of the diaphragm: △Lh=(Lh0-Lh) / Lh0×100%(Formula 2)

[0050] According to the present invention, the bonding performance between the separator and the positive electrode sheet is 10-60 N / m.

[0051] According to the present invention, the bonding performance between the separator and the negative electrode sheet is 10-60 N / m.

[0052] In the present invention, the test method of the bonding performance between the separator and the positive electrode sheet includes cutting the positive electrode sheet and the separator into 14cm×8.5cm, stacking the base film, the positive electrode sheet, and the coated separator in sequence, stacking 6-8 layers in sequence, and hot pressing for 60s at a temperature of 90°C and a pressure of 0.3MPa. After hot pressing, cut into 3cm strips, stretch at a speed of 300mm / min, and the data obtained is the bonding strength between the separator and the positive electrode, in N / m.

[0053] In the present invention, the test method for the adhesion performance between the separator and the negative electrode sheet is the same as the test method for the adhesion performance between the separator and the positive electrode sheet.

[0054] In the present invention, the high adhesion between the sodium ion battery separator and the positive electrode and the negative electrode can effectively prevent the sodium ion battery from deforming or softening, thereby improving the stability and safety of the sodium ion battery.

[0055] According to the present invention, the base film has a porous structure. Preferably, the average pore size of the porous structure is 30nm-80nm, preferably 40nm-50nm, and the porosity is 40-80%, preferably 40-60%.

[0056] In the present invention, for a certain electrolyte, a diaphragm with high porosity can effectively reduce the impedance of the battery, but the higher the porosity, the better. The higher the porosity, the worse the mechanical resistance and the anti-opening performance. Submicron pore size is extremely important for preventing the positive and negative electrodes of the battery from short-circuiting. However, the pore size should not be too large, otherwise the diaphragm will not play a role in preventing short-circuiting, affecting the safety performance of the battery.

[0057] According to the present invention, the base membrane is selected from at least one of PP membrane, PE membrane, cellulose membrane, PET membrane, PI membrane, PVDF membrane, PVDF-HFP membrane, and PTFE membrane; preferably selected from at least one of PP membrane, PE membrane, cellulose membrane, PET membrane, PI membrane, and PTFE membrane.

[0058] In the present invention, the base film has a high-temperature closed-cell function, which can prevent the battery from short-circuiting in time. The diaphragm retains this property of the base film. By applying a coating on both sides of the base film, the thermal stability and hot pressing bonding properties of the diaphragm are further improved, the internal resistance of the diaphragm is reduced, and the cycle performance of the sodium ion battery is thereby improved.

[0059] According to the present invention, the sodium ion solid electrolyte is selected from Na3Zr2Si2PO 12 , Na-β-Al2O3, Na-β”-Al2O3, Na3SbS4, and NaCl.

[0060] In the present invention, the addition of sodium ion solid electrolyte firstly has the effect of conventional inorganic materials on the anti-heat shrinkage of the diaphragm; secondly, compared with conventional inorganic materials, the solid electrolyte has good ion conductivity, which is beneficial to improve the internal resistance of the diaphragm. Therefore, the addition of sodium ion solid electrolyte is beneficial to improve the safety performance and cycle performance of the battery.

[0061] In the present invention, the surface density of the fluorinated polyimide microspheres in the coating is lighter than that of ordinary ceramics, which is beneficial to improving the energy density of the battery; the addition of the sodium ion solid electrolyte can play a role in replenishing sodium and reducing the internal resistance of the diaphragm. At the same time, the synergistic effect between the fluorinated polyimide microspheres and the sodium ion solid electrolyte effectively improves the thermal stability of the base film and has better safety performance.

[0062] According to the present invention, the gelable high molecular polymer is at least one selected from polyamide, polyimide, meta-aramid, para-aramid, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate and polyacrylonitrile.

[0063] In the present invention, the gelable high molecular polymer, on the one hand, plays the role of a binder in the entire formulation system, ensuring a good coating effect between the coating and the base film and preventing it from falling off; on the other hand, it has the characteristics of gelling, absorbing liquid and retaining liquid in the electrolyte, which is beneficial to the wetting of the diaphragm and improves the interface characteristics with the positive and negative electrodes and the risk of leakage.

[0064] According to the present invention, the plasticizer is selected from at least one of polyethylene oxide, polyvinyl alcohol, cyanoethyl polyvinyl alcohol, sulfonic acid polyvinyl alcohol and acrylonitrile.

[0065] In the present invention, the addition of plasticizer can improve the toughness of the coating to prevent the coating from cracking and falling off. On the other hand, the selected plasticizer can improve the pore-forming effect of the coating to a certain extent, improve the air permeability of the coated diaphragm to a certain extent, and reduce the internal resistance of the diaphragm.

[0066] In the present invention, the gelable high molecular polymer in the coating can make the prepared diaphragm have the characteristic of absorbing electrolyte gelation, and the synergistic combination with the plasticizer and fluorinated polyimide microspheres can simultaneously have good hot pressing bonding performance, which is beneficial to improving the interfacial cycle performance and leakage risk of sodium ion batteries.

[0067] A second aspect of the present invention provides a method for preparing a sodium ion battery separator, comprising the following steps:

[0068] (1) stirring and mixing a mixed solution of a gelable polymer and a plasticizer with a mixed dispersion of a sodium ion solid electrolyte and fluorinated polyimide microspheres to obtain a coating slurry;

[0069] (2) The coating slurry is coated on both sides of the base film, and the sodium ion battery separator is obtained after drying.

[0070] The method for preparing the sodium ion battery separator provided by the present invention adopts a low-boiling point organic solvent in combination with temperature and humidity oven drying to prepare the coating, and the process is simpler and the operation is convenient.

[0071] According to the present invention, the mass ratio of the gelable high molecular polymer to the plasticizer in step (1) is 90-95:5-10.

[0072] According to the present invention, the mass ratio of the sodium ion solid electrolyte to the fluorinated polyimide microspheres is 50-90:10-50.

[0073] According to the present invention, the total mass of the fluorinated polyimide microspheres and the sodium ion solid electrolyte is calculated as A, the total mass of the gelable high molecular polymer and the plasticizer is calculated as B, and the mass ratio of A:B is 50-90:10-50.

[0074] According to the present invention, the stirring and mixing conditions in step (1) include: a stirring speed of 500 r / min-1500 r / min, a stirring time of 0.5 h-3 h, and a stirring temperature of 5° C.-30° C.

[0075] In the present invention, the solid content of the coating slurry is 10-30%, preferably 15-25%. The solid content of the slurry is closely related to the stability of the slurry. Under the same process and formula, the higher the solid content of the slurry, the higher the viscosity, and vice versa. The higher the solid content, the shorter the stirring time of the slurry, the less solvent required, the higher the coating drying efficiency, and the time is saved. However, high solid content slurry may increase the loss strength of the equipment and increase the difficulty coefficient of coating.

[0076] According to the present invention, the coating in step (2) is selected from at least one of dip coating, precision spray coating, micro gravure roller coating, and wire rod coating.

[0077] In the present invention, the coating is selected from wire rod coating.

[0078] According to the present invention, the drying is selected as temperature and humidity oven drying, and the drying conditions include: temperature of 40° C.-80° C., humidity of 40%-80%.

[0079] In the present invention, the temperature and humidity of the temperature and humidity oven can be controlled to affect the replacement rate of the solvent and the non-solvent during the phase transformation of the polymer, thereby affecting the morphology of the coating. If the temperature is too high, the solvent evaporates quickly to form a closed layer on the surface, which will inhibit the volatilization of the lower solvent; if the temperature is too low, the drying performance is reduced, the coating does not dry and even forms a sagging phenomenon. Inappropriate humidity will affect the replacement efficiency of the non-solvent and the solvent, affect the phase transformation process, and then affect the morphology.

[0080] The third aspect of the present invention provides a sodium ion battery separator prepared according to the method described in the second aspect.

[0081] A fourth aspect of the present invention provides a sodium ion battery, wherein the sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm, and the diaphragm is the diaphragm described in the first aspect or the diaphragm described in the third aspect.

[0082] In the present invention, the positive electrode sheet is a layered oxide sodium iron manganate positive electrode sheet, the negative electrode sheet is a hard carbon negative electrode sheet, and the electrolyte includes ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and sodium hexafluorophosphate, wherein EC / EMC / DMC is 1:1:1, and the concentration of sodium hexafluorophosphate is 1.0 mol / L.

[0083] The sodium ion battery separator prepared by the method provided by the present invention has good thermal stability, low internal resistance of the separator and good hot pressing bonding performance. The sodium ion battery separator provided by the present invention can effectively improve the problems of poor cycle performance and electrolyte leakage during the use of the sodium ion battery, thereby improving the power safety of the sodium ion battery.

[0084] The present invention will be described in detail below through examples. In the following examples, the fluorinated polyimide microspheres are homemade in the laboratory, and the preparation method is as follows:

[0085] According to the molar ratio of 3,3',4,4'-dimethyl ketone tetracarboxylic dianhydride and sulfone-containing diamine 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]sulfone of 1:1.015, the sulfone-containing diamine was dissolved in a polar solvent, and the dianhydride was added in batches, and a polyamic acid solution was synthesized in an ice-water bath to prepare a polyamic acid solution with a solid content of 15%. Polyamic acid microspheres were prepared by electrostatic spraying in an electric field with an electric field strength of 1 kV / cm, and then placed in a high-temperature hot furnace, imidized at 300°C for 40 minutes, and naturally cooled to room temperature to obtain fluorinated polyimide microspheres, such as Figure 1 As shown, the average particle size of the fluorinated polyimide microspheres is about 0.7 μm-4 μm.

[0086] Example 1

[0087] 45 g of polyvinylidene fluoride (PVDF) and 5 g of cyanoethyl polyvinyl alcohol were added to acetone to obtain a mixed solution I; 100 g of biphenyl-type fluorinated polyimide microspheres and 100 g of sodium ion solid electrolyte Na-β"-Al2O3 were added to acetone to obtain a dispersion solution II; the mixed solution I was mixed with the dispersion solution II, and the mixture was stirred and dispersed at 10°C and 800 rpm for 3 hours to obtain the desired coating slurry, with a slurry solid content of 25%.

[0088] A 3 μm coating was applied on the upper and lower sides of the 9 μm PE separator using a wire rod coating process, and then dried in an 80°C / 80% temperature and humidity oven to obtain the required 3+9+3 battery separator, marked as S1.

[0089] Example 2

[0090] 47.5 g of polyvinylidene fluoride (PVDF) and 2.5 g of cyanoethyl polyvinyl alcohol were added to acetone to obtain a mixed solution I; 150 g of biphenyl-type fluorinated polyimide microspheres and 50 g of sodium ion solid electrolyte Na-β"-Al2O3 were added to acetone to obtain a dispersion solution II; the mixed solution I was mixed with the dispersion solution II, and the mixture was stirred and dispersed at 10°C and 800 rpm for 3 hours to obtain the desired coating slurry, and the slurry had a solid content of 25%.

[0091] A 3 μm coating was applied on the upper and lower sides of the 9 μm PE separator using a wire rod coating process, and then dried in an 80°C / 80% temperature and humidity oven to obtain the required 3+9+3 battery separator, marked as S2.

[0092] Example 3

[0093] 45 g of polyvinylidene fluoride (PVDF) and 5 g of cyanoethyl polyvinyl alcohol were added to acetone to obtain a mixed solution I; 100 g of biphenyl-type fluorinated polyimide microspheres and 100 g of sodium ion solid electrolyte Na-β"-Al2O3 were added to acetone to obtain a dispersion solution II; the mixed solution I was mixed with the dispersion solution II, and the mixture was stirred and dispersed at 10°C and 800 rpm for 3 hours to obtain the desired coating slurry, with a slurry solid content of 25%.

[0094] A 5 μm coating was applied on the upper and lower sides of the 9 μm PE separator using a wire rod coating process, and then dried in an oven at 80°C / 80% to obtain the required 5+9+5 model battery separator, marked as S3.

[0095] Example 4

[0096] The separator was prepared according to the method of Example 1, except that the sodium ion solid electrolyte was changed to Na3SbS4. The prepared battery separator was marked as S4.

[0097] Example 5

[0098] A separator was prepared according to the method of Example 1, except that the gelable high molecular polymer was changed to polymethyl methacrylate (PMMA). The prepared battery separator was marked as S5.

[0099] Example 6

[0100] A separator was prepared according to the method of Example 1, except that the plasticizer was changed to sulfonic acid polyvinyl alcohol. The prepared battery separator was marked as S6.

[0101] Comparative Example 1

[0102] A separator was prepared according to the method of Example 1, except that no fluorinated polyimide microspheres were added. The prepared battery separator was marked as D1.

[0103] Comparative Example 2

[0104] A separator was prepared according to the method of Example 1, except that no sodium ion solid electrolyte was added. The prepared battery separator was marked as D2.

[0105] Comparative Example 3

[0106] A separator was prepared according to the method of Example 1, except that no plasticizer was added. The prepared battery separator was marked as D3.

[0107] The air permeability, thermal stability, adhesion, diaphragm resistance and battery capacity retention rate of the prepared sodium ion battery of the diaphragms prepared in Examples 1-6 and Comparative Examples 1-3 were tested, and the results are shown in Table 1.

[0108] Air permeability test method:

[0109] According to GB / T 36363-2018 test standard for polyolefin separators for lithium-ion batteries, under the test temperature, humidity and normal pressure environment, the Wangyan air permeability tester applies a pressure of 1.12 kPa, and the area through which 100 mL of air passes is 6.45 cm 2 The sample size is 100mm×100mm, and the membrane is placed in the test head of the air permeability tester in a suitable range to test the air permeability. The average value of the three test results is taken as the air permeability of the membrane.

[0110] Thermal shrinkage test method:

[0111] Cut a square diaphragm of 10cm×10cm in size, locate 4 points at the center of the four sides 1cm away from the edges, and measure the distance between the two points in TD (transverse) and MD (longitudinal) through an optical microscope, and record them as Lh0 and Lz0. Then put 3 A4 papers on the top and bottom of the cut diaphragm and place it in a blast oven at a temperature of 150 (±1) degrees Celsius for 0.5h. After heating, take out the diaphragm, and after the diaphragm returns to room temperature, measure the distance between the two points in the transverse and longitudinal directions through an optical microscope again, and record them as Lh and Lz. Calculate the transverse and longitudinal shrinkage rates of the diaphragm according to the following formulas 1 and 2 respectively, and take the average of the three test results as the thermal shrinkage rate of the diaphragm.

[0112] Thermal shrinkage in the longitudinal direction of the diaphragm: △Lz=(Lz0-Lz) / Lz0×100%(Formula 1)

[0113] Thermal shrinkage in the transverse direction of the diaphragm: △Lh=(Lh0-Lh) / Lh0×100%(Formula 2)

[0114] Adhesion test method between diaphragm and positive / negative electrode:

[0115] The positive / negative electrode sheets were cut into 14cm×8.5cm, and the separator was of the same size. The positive / negative electrode and the separator coating were stacked together, separated by a base film, and 6-8 layers were stacked. The hot pressing conditions were 0.3MPa force, 90℃, and 60s time. After hot pressing, they were cut into 3cm strips and stretched at a speed of 300mm / min. The data obtained was the bonding strength between the separator and the positive / negative electrode, in N / m.

[0116] Test method for diaphragm resistance:

[0117] Cut 4 diaphragms that match the resistance test mold, put the diaphragms into an electrolyte with a concentration of 1.0 mol / L sodium hexafluorophosphate, ethylene carbonate (EC), and dimethyl carbonate (DMC) in a volume of 1:1:1, keep it sealed, soak for 2 hours, inject the electrolyte into the resistance test mold, put in one layer of diaphragms in turn, test its AC impedance resistance, put in another layer, test its AC impedance resistance, until 4 layers are put in, and measure the four AC impedance resistances R1, R2, R3 and R4 respectively. During the measurement process, it is necessary to ensure that the electrolyte in the resistance test mold can completely immerse the placed diaphragms.

[0118] Draw a curve with the number of membrane layers as the horizontal axis and the membrane resistance as the vertical axis, and find the slope and linear fit of the curve. When the linear fit is greater than 0.99, the ionic conductivity of the membrane is calculated according to the following formula. When the linear fit is less than 0.99, retesting is required:

[0119] R=k×1

[0120] Where:

[0121] R--Resistance value of 1 layer of diaphragm, in ohms (Ω)

[0122] k--The slope of the curve when the fitting degree is greater than 0.99.

[0123] Battery capacity retention rate test method:

[0124] At ambient temperature (25±5℃), charge at a constant current of 0.2C to a limit voltage of 3.95V, then change to constant voltage charging until the cutoff current reaches 0.01C, stop charging, leave for 5 minutes, and then discharge at a current of 1C to 2.0V as one cycle. Repeat 50 cycles and stop to measure the capacity retention rate.

[0125] Table 1

[0126]

[0127]

[0128] Table 1 (continued)

[0129]

[0130] It can be seen from the results in Table 1 that in Examples 1-6, the coating formula includes fluorinated polyimide microspheres, sodium ion solid electrolyte, gelable polymer and plasticizer, and the prepared coated diaphragm has good thermal stability, hot pressing bonding performance of positive and negative electrodes, high film breaking temperature and low diaphragm resistance. In Comparative Examples 1-3, the coating formula lacks one of fluorinated polyimide microspheres, sodium ion solid electrolyte and plasticizer, and the thermal shrinkage performance or air permeability value or positive and negative electrode bonding performance or film breaking temperature of the prepared diaphragm is somewhat different from that of the examples. Comparative Example 1 does not add fluorinated polyimide microspheres, and Comparative Example 2 does not add sodium ion solid electrolyte. The lateral yield and longitudinal shrinkage of Comparative Example 1 and Comparative Example 2 are significantly increased compared with the embodiment, and the thermal shrinkage performance is significantly reduced. When only sodium ion solid electrolyte is added or only fluorinated polyimide microspheres are added, the thermal shrinkage performance of the diaphragm is poor. Only when fluorinated polyimide microspheres and sodium ion solid electrolytes are added at the same time, the thermal stability of the diaphragm can be improved, indicating that the synergistic effect between fluorinated polyimide microspheres and sodium ion solid electrolytes effectively improves the thermal stability of the base film, and the safety performance is better. Comparative Example 3 does not add plasticizers, and the thermal stability and hot pressing bonding performance of the positive and negative electrodes are poor, indicating that plasticizers can assist other components, improve the thermal stability of the diaphragm and the hot pressing bonding performance of the positive and negative electrodes, and reduce the sodium ion battery interface cycle performance and leakage risk.

[0131] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A sodium ion battery separator, characterized in that: The diaphragm comprises a base film and coatings on both sides of the base film; the coatings comprise fluorine-containing polyimide microspheres, sodium ion solid electrolyte, gelable high molecular polymer and plasticizer.

2. The diaphragm according to claim 1, characterized in that The fluorinated polyimide microspheres have a glass transition temperature of 200-350° C., a melting point of >300° C., and an average particle size of 0.05-10 μm, preferably 0.7-4 μm.

3. The diaphragm according to claim 1 or 2, characterized in that: The mass ratio of the gelable polymer to the plasticizer is 90-95:5-10; And / or, the mass ratio of the fluorinated polyimide microspheres to the sodium ion solid electrolyte is 50-90:10-50; And / or, the total mass of the fluorinated polyimide microspheres and the sodium ion solid electrolyte is calculated as A, the total mass of the gelable high molecular polymer and the plasticizer is calculated as B, and the mass ratio of A:B is 50-90:10-50.

4. The diaphragm according to any one of claims 1 to 3, characterized in that: The thickness of the diaphragm is 9-52 μm; the thickness of the base film is 5-40 μm, and the thickness of the coating is 2-6 μm; Preferably, the thickness of the separator is 9-20 μm; the thickness of the base film is 5-12 μm, and the thickness of the coating is 2-4 μm.

5. The diaphragm according to any one of claims 1 to 4, characterized in that: The diaphragm is maintained at a temperature of 150° C. for 0.5 h, with a transverse shrinkage of 0-5% and a longitudinal shrinkage of 0-5%; And / or, the bonding performance between the separator and the positive electrode plate is 10-60N / m; And / or, the bonding performance between the separator and the negative electrode plate is 10-60N / m.

6. The diaphragm according to any one of claims 1 to 5, characterized in that: The base film has a porous structure; Preferably, the average pore size of the porous structure is 30-80 nm, preferably 40-50 nm, and the porosity is 40-80%, preferably 40%-60%.

7. The diaphragm according to any one of claims 1 to 6, characterized in that: The base membrane is selected from at least one of a PP membrane, a PE membrane, a cellulose membrane, a PET membrane, a PI membrane, a PVDF membrane, a PVDF-HFP membrane, and a PTFE membrane; Preferably, it is at least one of PP membrane, PE membrane, cellulose membrane, PET membrane, PI membrane and PTFE membrane.

8. The diaphragm according to any one of claims 1 to 7, characterized in that: The sodium ion solid electrolyte is selected from Na3Zr2Si2PO 12 , Na-β-Al2O3, Na-β”-Al2O3, Na3SbS4, NaCl; And / or, the gelable high molecular polymer is at least one selected from polyamide, polyimide, meta-aramid, para-aramid, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate and polyacrylonitrile; And / or, the plasticizer is selected from at least one of polyethylene oxide, polyvinyl alcohol, cyanoethyl polyvinyl alcohol, sulfonic acid polyvinyl alcohol and acrylonitrile.

9. A method for preparing a sodium ion battery separator, characterized in that: The following steps are involved: (1) stirring and mixing a mixed solution of a gelable polymer and a plasticizer with a mixed dispersion of a sodium ion solid electrolyte and fluorinated polyimide microspheres to obtain a coating slurry; (2) The coating slurry is coated on both sides of the base film, and the sodium ion battery separator is obtained after drying.

10. The method according to claim 9, characterized in that The mass ratio of the gelling polymer to the plasticizer in step (1) is 90-95:5-10; And / or, the mass ratio of the sodium ion solid electrolyte to the fluorinated polyimide microspheres is 50-90:10-50; And / or, the sum of the mass of the fluorinated polyimide microspheres and the sodium ion solid electrolyte is calculated as A, the sum of the mass of the gelable polymer and the plasticizer is calculated as B, and the mass ratio of A:B is 50-90:10-50; And / or, the stirring and mixing conditions in step (1) include: a stirring speed of 500 r / min-1500 r / min, a stirring time of 0.5 h-3 h, and a stirring temperature of 5° C.-30° C.

11. The method according to claim 9, characterized in that The coating in step (2) is selected from at least one of dip coating, precision spray coating, micro gravure roller coating, and wire rod coating; And / or, the drying in step (2) is selected as temperature and humidity oven drying, and the drying conditions include: temperature of 40° C.-80° C. and humidity of 40%-80%.

12. A sodium ion battery separator prepared by the method according to claims 9-11.

13. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is the separator according to any one of claims 1 to 8 and 12.

Citation Information

Patent Citations

  • Separator for single high-capacity polymer lithium ion battery and manufacturing method for separator

    CN105914322A

  • Polyimide microsphere slurry, composite separator and lithium ion battery

    CN109817870A

  • Novel polyimide microsphere slurry and coated diaphragm thereof

    CN114883746A

  • Solid sodium ion electrolyte membrane and preparation method thereof

    CN115799606A